Entwicklung und politische Rahmenbedingungendes ökologischen Landbaus in Europa; Development and Policy Environment for Organic Farming in Europe - Nicolas Lampkin; Susanne Padel; Carolyn Foster (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– The paper describes the development and policy environment of organic farming in the European Union, where organic farming has grown rapidly due to a variety of factors. Policy measures concerning area-based financial support for conversion to and continuation of organic farming, officially-recognized standards and support for market and regional development, advice and research are considered. This indicates that individual measures can also work against each other. In some countries, good experiences have been made with integrated action plans, an approach that is also being discussed at the European level and which could achieve a good basis for the development of organic farming in future.
Keywords: 330